Building Islamic Finance: Loyalty of Solo Students towards Sharia Banking with Social Environment Mediator - Sari, Tyas Kartika; Putri, Rizky Nur Ayuningtyas (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The objectives of this study examine the effect of financial literacy, trust, service quality, and customer satisfaction on student loyalty to Islamic banking with the social environment as a mediator. The research population is Muslim students in Solo who are Islamic banking customers, with a sample of 96 people. Quantitative research using SEM-PLS analysis through SmartPLS 4. The research shows that service quality has a significant positive influence on loyalty, while financial literacy has a significant positive effect on the social environment. However, the social environment cannot mediate the relation of the independent and dependent variable. This research is expected to provide implications for Islamic banking in designing strategies to effectively increase student loyalty.